(13b-6)-4(3b+1)=-7

Simple and best practice solution for (13b-6)-4(3b+1)=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13b-6)-4(3b+1)=-7 equation:


Simplifying
(13b + -6) + -4(3b + 1) = -7

Reorder the terms:
(-6 + 13b) + -4(3b + 1) = -7

Remove parenthesis around (-6 + 13b)
-6 + 13b + -4(3b + 1) = -7

Reorder the terms:
-6 + 13b + -4(1 + 3b) = -7
-6 + 13b + (1 * -4 + 3b * -4) = -7
-6 + 13b + (-4 + -12b) = -7

Reorder the terms:
-6 + -4 + 13b + -12b = -7

Combine like terms: -6 + -4 = -10
-10 + 13b + -12b = -7

Combine like terms: 13b + -12b = 1b
-10 + 1b = -7

Solving
-10 + 1b = -7

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 1b = -7 + 10

Combine like terms: -10 + 10 = 0
0 + 1b = -7 + 10
1b = -7 + 10

Combine like terms: -7 + 10 = 3
1b = 3

Divide each side by '1'.
b = 3

Simplifying
b = 3

See similar equations:

| 6/7c=18 | | 3x+6(2x-3)=4+7x | | -10-4x+(-4)=70 | | -12r=-5 | | 2(2-4)=3(z-4) | | 3w^3/4w*9/w | | 3/4c=12 | | 5x+6x+3+8=8x+5+2x | | 7x^2-400=0 | | x/5=3y+7 | | 2377960+26T=2067959+125T | | 10x^2+8.5X+5=0 | | 10Y=40 | | x+[x-4]+4[x-4]=52 | | -4+12t=100 | | 3x+2=-4x+23 | | y+2x=-3x+1 | | 9p+2=9+8p | | 2(2y-4)=12x | | 2(2y-4)=12x | | 2e-3.1=1.7 | | y=3x^3-3x^2 | | y-11=7 | | 2377960+26T=3000000 | | 7x+9y+17z=19y+13x+4z | | =24x^2-48x+16 | | 22x+80=30x | | 11/3x=22 | | 17-9m=1m-23 | | -0.25x-(-1.5)=10 | | 5(5x-5)=50 | | 7/4x=22 |

Equations solver categories